Subnational Competitiveness Grants Guidebook : A Tool to Promote Jobs and Economic Transformation in Cities and Regions through Performance-Based Financing - Salhab, Jade (World Bank, Washington, DC, 2022)
This report is a guidebook for practitioners to promote policy actions that strengthen competitiveness at the subnational level. It introduces Subnational Competitiveness Grants (SCGs) as an innovative approach in which well-tested tools for competitiveness policy and subnational government performance can be leveraged to advance the jobs and economic transformation agenda at the subnational level. SCGs are a type of intergovernmental fiscal instrument where fiscal transfers are provided to subnational governments to achieve improvements in competitiveness and local economic development. SCGs can enhance competitiveness by increasing the capacity, mandate, and incentives of subnational governments to affect relevant policy levers. This instrument builds on The World Bank’s 2015 report on Competitive Cities for Jobs and Growth which provided a conceptual framework on how cities and subnational regions can become more competitive and create economic growth and quality jobs. This guidebook first discusses the relevance of subnational governments in enhancing competitiveness and shows that performance-based fiscal transfers can be a useful tool in incentivizing and capacitating subnational governments to support local competitiveness in particular contexts. The second part of the guidebook provides detailed guidance on the appropriate design and implementation of this instrument. This guidebook will be relevant for a wide variety of policymakers and practitioners, including national and subnational governments, program designers, and others interested in subnational and city competitiveness.